Kinematic and kinetic differences between shod and barefoot running - Syrjälä, Jaakko (2016)
Syrjälä, J. 2016. Kinematic and kinetic differences between shod and barefoot running. Debartment of Biology of Physical Activity, University of Jyväskylä, Master´s Thesis in Biomechanics, 65 p.